Kajian Manfaat Kebijakan Pengujian Kendaraali Bermotor Di Sektor Perhubungan Kota Batam - Soedomo, R. Pramono (Warta Penelitian Perhubungan, 2010)
fJ1ch mode of transportation mrriers and 1micles with the tips and functions that hare rertain speciftaitionsare required far the testing of rehicles far rood 1oorthiness criteria to ensure the lerel of fil/ehJ, fmlrityand romfart an a public rood.For trnnces refemd to the test errn; re/ride leuies in~d leuies Motor Vehicle In~ in aa:ordancewith the I.aw nu nm 28 of 2009 on I.Deni T nxes mid l.£7. rit's.171e pu~ of this stu.dt; to determine the txJfential aaeptance of retribution test motor re11icles and theirrelation to the availabiliti; of public tranqxmation in the citi; of Batam. 111is resareh methodology descriptireanalysis approoch bt; rnlculating leut; rerenue growth associated number of rel1icles that mm1 out theobligations and view the relationship betnren W£r dmrges and the avaiUWility of public transportationfocilities in Batam.TI7e results of tl7e stu.dt; shmred tlmt tl1e nunm of public tmnSfXYrintion is relntirely much less tlum publictnmspm instead. Number of public transport in 2009 ns many as 5 710 units, not tl?e public tnmspm asmud1as15,166 units. For public transportation 11:as dominated bt; Taxi as mam; as 3221 units (5851 %),~let 1637 units (29. 74%) 11xis Bus of 641 units (11. 75%). From the aspect of local rerenue, leutj incomesince tlre l_Plr 2003 - 2009 shm~d good progress and p'.)Sifil:e iJnfXld an PAD. To improre the receptionarea, tlre test re/1icles are made to pril.xite re/rides in order to reduIE air pollution le7:els. s~ leutj tariffstrucks can re increaEed as a CXJ111fX?l15Cltion e:qm!X? of rood damage due to tlie mdJility of tlJe truck, whileoutside tl7e truck tariffs can re lo11ITed in order to mise mmrmess of motor rehicle testing.Keywords: Lem; Test Vehicle, Transportntion Batnm, Retribution, Public Transportation.